Reconfiguration of electrical distribution networks using the simulated annealing algorithm - Ñaupari Huatuco, Zocimo (2024)
This article presents a new algorithm to solve the distribution network reconfiguration problem using Simulated Annealing Optimization. The proposed method provides an improvement relative to the classic approach and the convergence rate between its simulations, using the Open Distribution System Simulator (OpenDSS) software. In addition, using the particular space mesh search concept, which considerably reduces the solution search space. The proposed algorithm aims to reduce energy losses in distribution networks; its operation was applied to the simple 5-bus system. Finally, the proposed algorithm was used for the 33-bus distribution test system, commonly found in the literature. The simulation results show that the proposed method is very efficient and guarantees the achievement of the global optimum.